Vectors for a choice: History of the Present Time and students’ research at the PPGH/UDESC (Tempo e Argumento, 2017)
This article is included in the commemorative edition celebrating 10 years of the Graduate Program in History of the Santa Catarina State University (PPGH/UDESC), created in 2007, which has been accompanied, since 2009, by the journal Tempo & Argumento. The text aims to: present the theoretical choices that marked out the program’s proposal, with a focus on History of the Present Time; identify the temporal and geographic approaches selected; and point out the methodological choices and the theoretical foci privileged in the MA dissertations submitted within this period. This article analyzes academic research as a vehicle to disseminate studies and debates from the perspective of History of the Present Time, a field under construction within the History area that has, at the UDESC, the first specific graduate program with this thematic proposal. Keywords: History of the Present Time. Santa Catarina State University. Graduate Program in History. Graduate Students.